2019
DOI: 10.1186/s13019-019-0979-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of argon plasma coagulation combined with cryotherapy for central airway stenosis caused by lung cancer

Abstract: Background: This study aimed to study the clinical efficacy of argon plasma coagulation plus cryotherapy for central airway stenosis caused by lung cancer. Methods: The clinical data of 177 patients with central airway stenosis caused by lung cancer received surgery from June, 2017 to July 2018 were retrospectively analyzed. According to different treatments, 43 patients received cryotherapy were included in the control group, while 134 patients received argon plasma coagulation plus cryotherapy were in the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Highly hydrated tissues are sensitive to cryotherapy. (4) In terms of immune functions, basic and clinical studies have confirmed that cryotherapy can significantly improve the contents of OKT3+ and OKT4+ and the ratio of OKT3+/OKT4+ in immune cells, significantly increase the expression of IL-2R, and improve the immune function of patients [ 4 , 5 ]. Cryotherapy has been widely used in various diseases in clinic with good outcomes, including prostate cancer [ 6 ], irreversible pulpitis [ 7 ], esophageal cancer [ 8 ], cervical cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highly hydrated tissues are sensitive to cryotherapy. (4) In terms of immune functions, basic and clinical studies have confirmed that cryotherapy can significantly improve the contents of OKT3+ and OKT4+ and the ratio of OKT3+/OKT4+ in immune cells, significantly increase the expression of IL-2R, and improve the immune function of patients [ 4 , 5 ]. Cryotherapy has been widely used in various diseases in clinic with good outcomes, including prostate cancer [ 6 ], irreversible pulpitis [ 7 ], esophageal cancer [ 8 ], cervical cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%